The Role of Music and Harmony of the Thai Society - Sukwin, Kraiwit (Journal of Music and Performing Arts Khon Kaen University, 2022)
Thai society is a multicultural society. Creating reconciliation among diverse social groups is an important issue. And music is a tool that has a role about the harmony of Thai society from the past. Music is a science that entertains people in the society. On the other hand, it has a role in healing the mind and build a good relationship. Therefore, this article aims to explain the relationship between the music role and harmony in Thai society. That includes the use of music as a tool to harmonize the unity of the people as well as music that is in the traditional way of life until causing the jealousy of the music keeper, it reflects the harmony of the people with music as the intermediary. Therefore, music has a role related to harmony in family institutions, educational institutions, religious institutions, political institutions and other institutions. Music applying to create harmony should consider a variety of contexts. And that music should not be difficult. That should use the folk music in the interest of the people. However, the role of music and harmony is applied in two ways: direct use, which directs people to participate in music; and indirect use, which use music for the performance.